2008
DOI: 10.1016/j.jpain.2008.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Pain Catastrophizing and Beliefs Predict Changes in Pain Interference and Psychological Functioning in Persons With Spinal Cord Injury

Abstract: The current study sought to examine how changes in pain-related beliefs and coping responses are related to changes in pain interference and psychological functioning in individuals with spinal cord injuries (SCI) and pain. To measure longitudinal changes in these variables, respondents completed a survey which included measures of pain intensity, pain interference, and psychological functioning, as well as specific psychosocial variables (pain-related beliefs, coping, and social support), and then completed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
60
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 49 publications
6
60
1
2
Order By: Relevance
“…32 Persons with SCI and pain experienced lower HSE and exercise SE than persons without pain. 33,38 High pain control was associated with less pain interference 39,40 and lower pain intensity, 40 while inconsistent relationships of SE with these variables were found. 32,33,38,41 Mental health.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…32 Persons with SCI and pain experienced lower HSE and exercise SE than persons without pain. 33,38 High pain control was associated with less pain interference 39,40 and lower pain intensity, 40 while inconsistent relationships of SE with these variables were found. 32,33,38,41 Mental health.…”
Section: Resultsmentioning
confidence: 98%
“…Persons with high GSE, HSE or pain control were consistently less anxious or depressed, [32][33][34]38,41,42 and reported better mental health. 39,40 However, these studies were cross-sectional and statements about the direction of relationships or causality cannot be made.…”
Section: Resultsmentioning
confidence: 99%
“…Among the many studies of individuals with spinal cord injury pain, veterans with the condition appear to have higher levels of pain catastrophizing than non-veterans (Ullrich, Jensen, Loeser, Cardenas, & Weaver, 2008). While most of these studies are cross-sectional in nature, a prospective study of people with spinal cord injury with chronic pain found that over a six month period decreases in pain catastrophizing were associated with decreased pain interference and improved psychological functioning (Hanley, Raichle, Jensen, & Cardenas, 2008). Conversely, a similar study in phantom limb pain found that pain catastrophizing at one month following amputation (that is, before chronic pain had developed) was predictive of decreased depressive symptoms and pain-related interference at both 12 and 24 months (Hanley, et al, 2004).…”
Section: Cognitive Responses To Painmentioning
confidence: 99%
“…Perceived control over pain has also been investigated, and there is less extensive evidence to support its role in relation to psychological functioning and disability in those with chronic pain secondary to physically disabling conditions. A study of people with spinal cord injury related chronic pain found that increases in perceived control over pain in a six month period was related to decreased pain intensity and pain interference, as well as increased psychological functioning, although the former was a non-significant finding (Hanley, et al, 2008). External locus of control in relation to pain as also been positively associated with depression among people with spinal cord injury related pain (Wollaars, et al, 2007).…”
Section: Cognitive Responses To Painmentioning
confidence: 99%
See 1 more Smart Citation